Hubungan Faktor Genetik dan Gaya Hidup dengan Miopia pada Mahasiswa Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa - Putu Nita Cahyawati; I Putu Rustama Putra; I Putu Arya Suryanta Wiguna (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
[Relationship of genetic and lifestyle factors with myopia in students of the Faculty of Medicine and Health Sciences, University of Warmadewa ] Myopia is a common disease with a high prevalence in the world, and is one of the refractive disorders, common in children and adults. Risk factors for myopia are genetics and lifestyle factors, especially close-up viewing activities. The aim of this research is to determine the relationship between genetic and lifestyle factors and myopia in students at the Faculty of Medicine and Health Sciences, Warmadewa University. The research design used was observational analytic with a cross sectional design. The research was conducted at the Faculty of Medicine and Health Sciences, Warmadewa University with a total sample of 132 people with inclusion criteria, namely students at the Faculty of Medicine and Health Sciences, Warmadewa University and willing to take part in the research and exclusion criteria, namely not coming during the research and having a history of congenital eye disorders. Data was obtained using a questionnaire. Data were analyzed univariately and bivariately using the chi-square test with a confidence level of 95% and results were significant if the p value was â‰¤0.05. And the results obtained are that the incidence of myopia in FKIK Unwar students is 74.2%, there are 93.9% of FKIK Unwar students who have genetic factors for myopia, there are 64.4% of FKIK Unwar students who have a lifestyle at high risk of myopia, and There is a relationship between genetic factors and myopia, but there is no relationship between lifestyle and myopia.